Solution-processed boron subphthalocyanine derivatives as acceptors for organic bulk-heterojunction solar cells1. Issue 14 (14th April 2015) - Ebenhoch, Bernd; Prasetya, Nor B. A.; Rotello, Vincent M.; Cooke, Graeme; Samuel, Ifor D. W.
<x xml:space="preserve">Abstract</x> We present solution-processed organic solar cells based on subphthalocyanine acceptors with strong light harvesting in the visible region and an efficiency up to 3.5%.